2009
DOI: 10.3892/or_00000625
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of tetramethylpyrazine on P-gp, MRP2, MRP3 and MRP5 in multidrug resistant human hepatocellular carcinoma cells

Abstract: Abstract. Some membrane transporters in liver, such as P-glycoprotein, multidrug resistance-associated protein 2 (MRP2), MRP3, and MRP5 can lead to a complex multidrug resistance (MDR) to antineoplastic agents. How to inhibit these proteins is still an issue. Tetramethylpyrazine is a bioactive constituent isolated from the root of Ligusticum chuanxiong Hort, a Chinese herb. Recent studies showed that it can enhance the chemosensitivity effects of a drug on human hepatocellular carcinoma cells, acting as a mult… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(5 citation statements)
references
References 20 publications
0
5
0
Order By: Relevance
“…Tetramethylpyrazine (TMP) is an alkaloid monomer isolated from Ligusticum chuanxiong hort (Chen et al, 2018). A series of studies have shown that TMP possesses a variety of antitumor effects including the inhibition of tumor cell proliferation, invasion, and drug resistance (Wang et al, 2010). Reports have demonstrated that TMP administration induces apoptosis and autophagy in hepatocellular carcinoma (Cao et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Tetramethylpyrazine (TMP) is an alkaloid monomer isolated from Ligusticum chuanxiong hort (Chen et al, 2018). A series of studies have shown that TMP possesses a variety of antitumor effects including the inhibition of tumor cell proliferation, invasion, and drug resistance (Wang et al, 2010). Reports have demonstrated that TMP administration induces apoptosis and autophagy in hepatocellular carcinoma (Cao et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Ligustrazine induces the expression of the metabolizing enzyme CYP3A4 via PXR 454 . The mRNA and protein levels of MDR1, MRP2, MRP3 and MRP5 were decreased after treatment with ligustrazine 455 . In addition, senkyunolide G inhibited OAT1, OAT2 446 .…”
Section: Tcms For the Treatment Of Covid-19 Infectionsmentioning
confidence: 94%
“…Glaucine not only functioned as inhibitor of transporters but also reduced the expression of MDR1 and MRP1 (Lei et al, 2013) while the isoquinoline alkaloids berberine and coptisine, mediated the expression of P-gp (Lin et al, 1999a). Tetramethylpyrazine downregulated the expression of MDR1, MRP2, MRP3 and MRP5 in BEL-7402/ADM cells (Wang et al, 2010). It has also reduced the expression of MDR1 and MRP1 in MCF-7/Dox and Pumc-91/ADM cells, respectively (Zhang et al, 2012;Wang et al, 2016).…”
Section: Phytochemicals Modulating Transporter or Protein Expressionmentioning
confidence: 99%